Risk factors of injury among urban adolescent students - Shabnam Imam; Nadira Begum; Farhana Salim; Mohammed Mustafizur Rahman; Meherunnesa Begum (International Journal Of Community Medicine And Public Health, 2023)
Background: Injuries are a significant public health issue and a leading cause of morbidity and mortality among adolescents. This study aimed to observe the incidence and risk factors of injury among urban adolescent students. Methods: The study was conducted at Dhanmondi high school in Dhaka, Bangladesh, from January to June 2018. A total of 325 students were purposefully selected for the study. The prevalence of injury, the pattern of injury, the socioeconomic and demographic characteristics, and the proportion of social determinants of injury were estimated. Results: 60% of the participants reported an injury in the last 6 months, with moderate injuries being the most common (63.59%). Seeking care was through visiting a doctor (28.72%) or hospital (33.33%). Most injuries occurred at home (33.33%) or in an institution of education (31.28%). The most common site of injury was the hand (39.49%) and the most common mode was sudden attack or fighting (28.21%). A significant association was found between injury occurrence and sex, grade of students, and age of students, but not with monthly income, education level of the father, occupation of the mother, or number of family members. Conclusions: The most prevalent risk factors for injury were fighting, violating traffic laws, and taking risks while getting into a vehicle. These factors were also statistically significant predictors of injury occurrence. The findings suggest a need for targeted injury prevention programs to address these risk factors among urban adolescent students in Bangladesh.